Kinerja Keuangan, Abnormal Return Sebelum dan Setelah Pengumuman Merger - Sumantri, Farid Addy (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
This study aims to examine the differences infinancial performance and abnormal returns in the period before and after the announcement of the merger of the companies listed on the Stock Exchange in the period 2004-2013. In this study the measurement of financial performance using four financial ratios which are the current ratio (CR), the net profit margin (NPM), return on equity(ROE) and price earnings ratio (PER), while the abnormal return is measured using the market return and the actual return. This study used purposive sampling in the sampling study. Company samples tested here are 8 companies from various different types of industries. Hypothesis testing is performed using paired sample t test with a confidence level of 5%. The test results of financial performance in the proxy with the current ratio (CR), the net profit margin (NPM), return on equity (ROE) and price earnings ratio (PER) its how sthe difference before and after the announcement of the merger on the companies listed on the Stock Exchange period 2004-2013.